THE EFFECT OF PROFIT MANAGEMENT AND THE FED’S INTEREST RATES ON FOREIGN INVESTMENT BEHAVIOR AND ITS IMPACT ON STOCK RETURNS IN THE BANKING SUBSECTOR ON THE IDX - Randy Yonathan (Jurnal Scientia, 2023)
This study aims to determine the effect of the Fed's profit and interest rate management on foreign investment behavior and its impact on the return of banking subsector stocks on the IDX. The type of research used is quantitative research, which is carried out to test research hypotheses through the stages of data collection, data processing, data analysis and statistical hypothesis testing. Quantitative research uses a causality design. The results of this research state that profit management does not have a significant effect on foreign investment behavior in the banking industry in 2018 – 2022, but the fed interest rate does not have a significant effect on foreign investment behavior in the banking industry in 2018 – 2022, profit management does not have a significant effect on stock returns in Banking in 2018 - 2022, the Fed'sinterest rate has a positive and significant effect on stock returns in Banking in 2018 - 2022, fotrusted investment behavior has a positive and significant effect on stock returns in the Banking in 2018 – 2022, profit management does not have a significant effect on stock returns through the mediation of foreign investment behavior in the Banking in 2018 – 2022 and the Fed's interest rate does not have a significant effect on stock returns through mediation foreign investment behavior in Banking in 2018 - 2022.